Young Families' Financial Stress: The Importance of Financial Management Behavior with Income as Control Variable - Islami, Fajrina Noor; Renanita, Theda (Universitas Muhammadiyah Surakarta, 2025)
Abstract. Achieving financial well-being is a universal aspiration among families. However, data indicate that numerous families in Indonesia continue to experience financial stress, partially attributed to financial management behavior. This study aims to investigate the effect of financial management behavior dimensions on financial stress among young families, while controlling for income levels. Employing a quantitative approach, the study involved 186 newly married participants with a marriage duration of five years or less, selected using purposive non-probability sampling. Primary data were collected through an online questionnaire utilizing the APR Financial Stress Scale and the Financial Management Behavior Scale. The study proceeded in two phases: instrument validation and model testing. Confirmatory Factor Analysis (CFA) was used for validation, while path analysis was conducted using Mplus version 8.3. CFA results indicated good model fit based on RMSEA, CFI, TLI, SRMR, and factor loadings exceeding 0.30. Path analysis revealed that, after controlling for income, cash and credit management significantly predicted financial stress, whereas saving, investment, and insurance behaviors did not. These findings suggest that educational initiatives focusing on cash flow and credit management may assist newly married couples in adopting more prudent financial practices.